Guiding the Way: Facilitating Requirements Elicitation with Selection Universe Approach - Meireles, Maria Alcimar Costa; Magalhães, Juliana; Barauna, Nasthya; Rocha, Sabrina; Maldonado, Jose Carlos; Conte, Tayana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3338, 2024)
Context: Requirements Engineering is crucial in software development, and Design Thinking (DT) emerges as an alternative to improve it, especially in requirements elicitation. The literature reports the utility of DT in this activity, offering a large number of techniques, although choosing one of them can be challenging. To mitigate this challenge, we propose the Selection Universe, an approach that assists in selecting among the DT techniques available. Goal: To present how the Selection Universe can support selecting the DT techniques for requirements elicitation. Method: Two empirical studies were conducted to evaluate the approach. The first study involved undergraduate students and utilized the techniques focus groups and card sorting. The second study was conducted with industry professionals and utilized the technique questionnaire. Results: The focus group application revealed that the approach helped selecting techniques by objectively demonstrating what was necessary to use the technique and the outcome it would generate. The card sorting revealed the need to change the nomenclature of one of the approach’s categories. The questionnaire technique highlighted that the approach facilitates requirements elicitation and technique selection, providing an overview of each technique. Conclusion: These studies revealed that the Selection Universe supports the requirement’s elicitation stage, as the approach provides a clearer understanding of the DT techniques, thus facilitating the best choice amongst them.